Macroeconomic factors affecting Malaysia's deficit trade balance with China / Mohammad Nor Syafik Noor Hamidi - Noor Hamidi, Mohammad Nor Syafik (2018)
Bilateral trade balance between countries is one of the indicator to measure the level of economy development for that country. Although total global value of Malaysia's trade balance showing uptrend throughout the years, but bilateral trade balance with China shows deficit for quite few years. This study objective is to investigate the macroeconomic factors that are consist of Real Exchange Rate (RER) in RM/Yuan, Government Expenditure (GOV) in RM and Oil Prices (OP) in RM that affecting the Malaysia's deficit trade balance with China. The data obtained is from Malaysia's data from January 2013 to May 2018. It is found that real exchange rate and oil prices are the factors affecting Malaysia's deficit trade balance with China except for government expenditure that is not affecting the dependent variable at all.